Father Involvement in Children’s English Learning at Home - Khairunnisa, Nadea Zulfa; Pamuji, Kukuh Dwi (English Education Study Program FKIP Universitas Alwashliyah Medan, 2025)
This study scrutinizes fathers' involvement in children's English learning at home. Employing a case study, this study involved four fathers aged between 31 and 45. The data were collected using in-depth interviews. The findings of the study indicate that there are several inhibiting and supporting factors for parenting self-efficacy (PSE). These factors include support and communication with partners, child characteristics, media influence, knowledge and education, culture and social values, and workload. In addition, PSE contributes to fathers' involvement in English learning at home. PSE can also be a protective factor from various obstacles and resource limitations. Fathers with high PSE can turn challenges into opportunities. This study also reveals that fathers' involvement efforts still need to be improved so that family functioning will be more optimal.